Old Traps for New Players: Western Direct Retailing Investment in Emerging Asian Markets - Mandhachitara, Rujirutana (International Review of Management and Marketing, 2014)
This paper is intended to provide a heads-up to transnational corporate executives who have an interest in, or responsibility for, foreign direct investment positions. Until relatively recently, many emerging markets in Asia restrict foreign participation in their retail sectors. Without sufficient pre-market entry information, Asia was identified as a particularly attractive region for western direct retail investment (WDRI). Groceries and provisions (FMCG) shoppers were served only by the traditional overseas Chinese retail trade. The western chains, principally from the United States and Europe, came to Asia in waves and unexpectedly experienced very high rates of attrition, explained in part by an indigenous account-payable-to- suppliers system referred to as Buy 10, Sell 7, Pay 3, Profit 4 (BSPP). A specific geographical focus of this paper is Thailand where foreign retailing casualties have been bloody. The ongoing lessons for executives of WDRI in entering emerging markets are addressed, particularly in relation to hidden local accounting traps. The implications for western retail investors in India’s recently-liberalized market are also discussed. Keywords: Retailing in emerging market; traditional and modern retail trade formats; direct retailing investment and accounts payable JEL Classifications: L81